Right aortic arch with isolation of the left subclavian artery: a rare association with airway obstruction - Yubbu, Putri; Abdul Latiff, Haifa; Adam Abbaker, Abdel Moneim (Cambridge University Press, 2017)
We present two interesting cases of isolated left subclavian artery from the pulmonary artery with symptoms of upper airway obstruction. The first patient had tetralogy of Fallot, pulmonary artery sling, bilateral superior caval veins, and left bronchial isomerism, suggesting heterotaxy syndrome. The second patient had a right aortic arch, isolated left subclavian artery, and bilateral arterial ducts. These two cases are interesting because of their rarity and uncommon presentation.